Spectrum of offending drugs and cutaneous adverse drug reactions requiring hospitalisation in a tertiary South African hospital in TB/HIV endemic setting - Konyana, S. P. P.; Teixeira, N. F.; Pirjol, L.; Thwala, B.; Nkoyane, W.; Porter, M.; Gxolo, F.; Phillips, E.; Lehloenya, R.; Mankahla, A.; Peter, J. (Frontiers in Allergy, 2024)
IntroductionCutaneous immune-mediated adverse drug reactions are more prevalent in people with human immunodeficiency virus (PWH). Severe cutaneous adverse drug reactions (SCAR) are a life-threatening subset of cutaneous adverse drug reactions (CADRs) and a significant public health issue in settings endemic for human immunodeficiency virus and tuberculosis. However, limited data are available on CADR requiring hospitalisation in African settings. The aim of this study is to describe the epidemiology, offending drugs and outcomes of CADRs requiring admission to a South African tertiary dermatology service.MethodsRetrospective folder review was conducted on all CADRs requiring hospitalisation at Nelson Mandela Academic Hospital in Mthatha, Eastern Cape, South Africa between 30 July 2015 and 15 December 2022. This data was compared to prospective inclusion of CADR admissions between 03 March 2021 and 09 April 2024 as part of the Immune-Mediated Adverse Drug Reactions (IMARI) Registry and Biorepository and AFRISCAR consortium. Where possible, phenotype and drug causality assessment was performed through RegiSCAR, or Naranjo and/or ALDEN scoring respectively.ResultsCADR admissions included 122 cases: 89 and 33 in the retrospective and prospective cohorts respectively. The commonest SCAR phenotype was Stevens-Johnson syndrome/toxic epidermal necrolysis (SJS/TEN) at 59.8% (73/122), although other validated SCAR phenotypes included drug reaction with eosinophilia and systemic symptoms (DRESS), acute generalized exanthematous pustulosis (AGEP) and generalized fixed bullous drug eruption (GBFDE). Cutaneous presentations included typical and atypical SCAR features against a background Fitzpatrick skin tones of type IV and above. Amongst the retrospective cohort 16.9% (15/89) of phenotypes were unclassifiable due to lack of photographs. The overall median (IQR) age was 38 (25–50) years, 50.8% (62/122) were male and 60.7% (74/122) were PWH [median (IQR) CD4T-cell count of 267 (76–470) cells/mm3]. The commonest offending drugs included cotrimoxazole in 24.6% (30/122); and anti-retroviral therapy (ART) in 13.9% (17/122). No offending drug could be identified in 24.7% (22/89) of the retrospective cohort. The median (IQR) length of hospital stay for validated SCAR was 13 (8–21) days for the retrospective cohort and 19 (13–28) days for the prospective cohort (p = 0.03). The median (IQR) length of hospital stay for non-SCAR was 9 (5–13) days for the retrospective cohort and 11 (9–16) days for the prospective cohort.ConclusionTypical and atypical presentations of SCAR were represented in this vulnerable South African cohort of predominantly PWH. SJS/TEN was the commonest phenotype, and cotrimoxazole the most frequent offending drug. This data emphasises the need for prospective data collection across a diverse African population for valid SCAR phenotyping and drug causality assessment.